EDUCATIONAL QUALITY ISSUES IN THE PROCESS OF INTRODUCING DIGITAL TECHNOLOGIES INTO THE MODERN EDUCATIONAL SYSTEM (Universal International Scientific Journal, 2026)
This article is aimed at analyzing educational problems that may arise during the introduction of digital technologies in the modern education system. Our study examines the impact of digital transformation on the efficiency of the education system, its shortcomings, and pedagogical mechanisms aimed at preventing them.
Keywords: : digital transformation, distance learning, digital literacy, pedagogical competence, innovative technologies, assessment system